Kontrak Kerja Pemanfaatan Dana Alokasi Non Fisik Tahun 2022 dalam Upaya Penurunan Jumlah Stunting oleh Badan Pengendalian Penduduk dan Keluarga Berencana di Kabupaten Manggarai - Maksimiliani Maria Saputri; Orpa J. Nubatonis; Yossie M.Y. Jacob (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The purpose of this study is the work contract for the utilization of non-physical allocation funds in 2022 in an effort to reduce the number of stunting by the Population Control and Family Planning Agency in Manggarai Regency. The type of research used is empirical research, which examines the Work Contract, Rights and Obligations of the utilization of Non-Physical DAK. The approach used is a qualitative approach as a research procedure that produces descriptive data in the form of oral written words from the people and actors observed. The types of data used are secondary data and primary data. The data collection techniques used are through literature study, interviews and field observations. The results of this study indicate that the implementation of the work contract for utilizing the Non-Physical Allocation Fund in an effort to reduce the number of stunting in the Manggarai Regency area. The impact of the distribution of the Non-Physical Allocation Fund channeled through BKKBN in an effort to reduce stunting in Manggarai Regency.